Genotypes and population genetics of cryptococcus neoformans and cryptococcus gattii species complexes in Europe and the mediterranean area - (:unkn) unknown (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2019)
A total of 476 European isolates (310 Cryptococcus neoformans var. grubii, 150 C. neoformans var. neoformans, and 16 C. gattii species complex) from both clinical and environmental sources were analyzed by multi-locus sequence typing. Phylogenetic and population genetic analyses were performed. Sequence analysis identified 74 sequence types among C. neoformans var. neoformans (VNIV), 65 among C. neoformans var. grubii (56 VNI, 8 VNII, 1 VNB), and 5 among the C. gattii species complex (4 VGI and 1 VGIV) isolates. ST23 was the most frequent genotype (22%) among VNI isolates which were mostly grouped in a large clonal cluster including 50% of isolates. Among VNIV isolates, a predominant genotype was not identified. A high percentage of autochthonous STs were identified in both VNI (71%) and VNIV (96%) group of isolates. The 16 European C. gattii species complex isolates analyzed in the present study originated all from the environment and all belonged to a large cluster endemic in the Mediterranean area. Population genetic analysis confirmed that VNI group of isolates were characterized by low variability and clonal expansion while VNIV by a higher variability and a number of recombination events. However, when VNI and VNIV environmental isolates were compared, they showed a similar population structure with a high percentage of shared mutations and the absence of fixed mutations. Also linkage disequilibrium analysis reveals differences between clinical and environmental isolates showing a key role of PLB1 allele combinations in host infection as well as the key role of LAC1 allele combinations for survival of the fungus in the environment. The present study shows that genetic comparison of clinical and environmental isolates represents a first step to understand the genetic characteristics that cause the shift of some genotypes from a saprophytic to a parasitic life style.
Keywords: Cryptococcus neoformans; Cryptococcus gattii; MLST; Population genetics; Europe; VAR. GRUBII; EPIDEMIOLOGY; INFECTION; NICHE; HIV